Factors influencing adoption of cryptocurrency-based transaction from an Islamic perspective - Al-hussaini, Al-hussaini Abulfathi Ibrahim Saleh; Ibrahim, Adamu Abubakar; Noordin, Mohamad Fauzan; Mohd Mohadis, Hazwani (Global Journals, 2020)
This paper presents a user study of “perception of the cryptocurrency-based transaction from the Islamic views”. The motivation lies with the fact that some users of cryptocurrency-based transaction raised concern on the nature of transactions with Bitcoin. Specifically, some argued that Bitcoin can be easily used for illegal purposes. Therefore, “Technological Acceptance Model” was adopted and quantitative research methodology was utilized, to formulate and test some hypothesis that will lead to an establishment of a model. Sample of 306 participants was used in the study. The result of the hypothesis testing indicates that “Behavioral Intention to Use Cryptocurrency from the Islamic perspective” is influenced directly by Shari’ah Compliance, Perceived Ease of Use, Emotionality, Perceived Usefulness, and Financial Concern. As evident from the analysis, Emotionality is influenced directly by Financial concern and Shari’ah Compliance. Whereas, Behavioral Intention is influenced indirectly by Financial Concern. The sample is general and does not specify a specific group of study. This study has contributed to understanding the Islamic issues behind the implementation of Cryptocurrency. This study adopted